System for the recovery and reuse of gray water water saving in public restrooms of companies in Peru. companies in Peru (LACCEI, 2024)
The research was conducted and executed in Peru, at Escalabs. the company Escalabs, the effect of the greywater recovery and reuse and reuse of gray water in water saving, The thesis was carried out using a non-experimental design, descriptive transversal design. With non-probabilistic sampling by expert judgment. expert judgment. The data collection was done with the technique of non-participant systematic observation, for the non-participant type, and descriptive statistics were used to analyze the data. descriptive statistics was used to analyze the data. the worrisome panorama of water scarcity, which is worsening with time, the reuse of greywater the reuse of graywater represents a good opportunity to optimize water use opportunity to optimize the use of water. the effect of the greywater recovery and reuse system on the the effect of the gray water recovery and reuse system on water savings in a bathroom in a bathroom of the Escalabs company, where it was determined that a 14.20% saving of 14.20% savings in water consumption, with an economic benefit o Translated with www.DeepL.com/Translator (free version)